Gender and cooperation in children: experiments in Colombia and Sweden (2012)
This paper compares cooperation among Columbian and Swedish children aged 9-12. We illustrate the dynamics of the prisoner's dilemma in a new task that is easily understood by children and performed during a physical education class. We find some evidence that children cooperate more in Sweden than in Colombia. Girls in Colombia are less cooperative than boys, whereas our results indicate the opposite gender gap in Sweden. On average, children are more cooperative with boys than with girls.